Endo‐allopolyploidy of autopolyploids and recurrent hybridization—A possible mechanism to explain the unresolved Y‐genome donor in polyploid Elymus species (Triticeae: Poaceae). Issue 2 (22nd August 2020) - Liu, Quan‐Lan; Liu, Lu; Ge, Song; Fu, Li‐Ping; Bai, Shi‐Qie; Lv, Xin; Wang, Qian‐Kun; Chen, Wang; Wang, Fan‐Ye; Wang, Li‐Hong; Yan, Xue‐Bing; Lu, Bao‐Rong
Abstract: The genus Elymus L. in the tribe Triticeae (Poaceae) includes economically and ecologically important forage grasses. The genus contains the pivotal St genome from Pseudoroegneria in combination with other genomes in the tribe. Many Elymus species are tetraploids containing the StY genomes. It is thought that polyploidization characterizes the speciation of the genus in which the Y is considered as another key genome. Based on data from cytological, genome in situ hybridization, and molecular studies, we hypothesized an endo‐allopolyploidy origin of the StY‐genome species from the autotetraploid Pseudoroegneria species. To test this hypothesis, we amplified, cloned, and sequenced five single‐copy nuclear genes (i.e., alcohol dehydrogenase 1–3, Adh1–Adh3, RNA polymerase II, Rpb2 ; and Waxy ) from Elymus, Pseudoroegneria, and Hordeum species. The phylogenetic trees constructed based on the sequencing analyses of all genes indicated that diploid and autotetraploid Pseudoroegneria species were closely related, although with considerable genetic variation in tetraploids. In addition, the StY‐genome Elymus species tended to have a close relationship with the diploid and autotetraploid Pseudoroegneria species, although different phylogenetic relationships among the gene trees were detected. These results indicated that the StY‐genome species may have an autotetraploid origin and experienced recurrent hybridization. The complex St genomes in Pseudoroegneria in the polyploid state may gain more opportunities for within‐species differentiation and recurrent hybridization. As a result, series modified versions of St genomes evolved into the StY genomes in some Elymus species. Abstract : The mixed Pseudoroegneria genomes maintained in a polyploid state may provide an opportunity to produce a modified St genome. As a result, the modified versions of St genomes can differentiate into StY genomes in some Elymus species. Therefore, we hypothesized an endo‐allopolyploidy origin of the StY‐genome species from autotetraploid Pseudoroegneria species.